Pharmacist as the Living Martindale; Power of Knowledge on antiviral information to prevent further spread and prompt treatment of COVID-19 Patients - Nik Mohamed, Mohamad Haniki (2021)
Explain life cycle of SARS-CoV-2 and potential drug targets. Discuss information regarding antivirals for Covid-19.